Dynamic Tissue—Specific Transcriptome Changes in Response to Verticillium dahliae in Wild Mint Species Mentha longifolia - Kelly J. Vining; Iovanna Pandelova (Plants, 2022)
Mentha longifolia is a wild mint species being used as a model to study the genetics of resistance to the fungal wilt pathogen Verticillium dahliae. We used high-throughput Illumina sequencing to study gene expression in response to V. dahliae inoculation in two M. longifolia USDA accessions with contrasting phenotypes: wilt-resistant CMEN 585 and wilt-susceptible CMEN 584. Roots and stems were sampled at two early post-inoculation time points, four hours and twenty-four hours, and again at ten days and twenty days post-inoculation. Overall, many more genes were differentially-regulated in wilt-resistant CMEN 585 than in wilt-susceptible CMEN 584. The greatest numbers of differentially expressed genes were found in the roots of CMEN 585 at the early time points. Specific genes exhibiting early, strong upregulation in roots of CMEN 585 but not in CMEN 584 included homologs of known plant defense response genes as well as genes involved in monoterpene biosynthesis. These genes were also upregulated in stems at the later time points. This study provides a comprehensive view of transcription reprogramming in Verticillium wilt-resistant mint, which will be the basis for further study and for molecular marker development.